Mathematics Education in the light of critical theory emerging from the Frankfurt School: discourses and meanings - Lucas Martini; Elenilton Vieira Godoy (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This research realizes a mapping of the Theses and Dissertations present in the catalog of Theses and Dissertations of CAPES and the Brazilian Library of Theses and Dissertations, proposing a quantitative and qualitative analysis. Next, we use Wiggershaus (2002) as the central axis for obtaining the meanings produced by the Frankfurt School. Throughout the text, we use the theoretical and methodological bias of Discourse Analysis in the light of Orlandi (2012, 2017). The general objective of this research is to search for senses produced from the conceptions of critical theory in research in Mathematics Education and the Frankfurt School. As a result, the research converges to a problematization of the rationality potentially developed by the teaching of mathematics, when supported exclusively in formulas and relations, can gradually veto critical rationality.